Impact measurement and tracking in a climate context. Support pack for agribusiness. - Giombini, Valentina; Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This slide deck report collects guidance and resources that complement training materials on impact measurement and tracking in a climate context.